Study of effectiveness, tolerability and safety of intravenous iron sucrose in iron deficiency anaemia in postnatal women - Niranjana, R.; Rajeswari, K. S. Raja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Iron deficiency anaemia is the most common type of reversible anemia encountered during pregnancy and postpartum period. The present study was done with the objective to find out the efficacy and safety of intravenous iron sucrose in the treatment of iron deficiency anaemia in the postpartum period. Methods: Fifty (50) postnatal patients both after vaginal and caesarean section with iron deficiency anaemia within the first 48 hours with haemoglobin percentage between 6 g/dl and 8g/dl were studied prospectively at the Institute of Obstetrics and Gynaecology, Madras Medical College, Chennai. The patients were given 100 mg of elemental iron diluted in 100 ml of 0.9% normal saline and infused over 15 minutes every alternate day (not more than 3 days in a week) until the required dosage is infused. The blood samples of all the patients were collected and analyzed for haemoglobin (g/dl), hematocrit, mean corpuscular volume (MCV), serum iron, total iron binding capacity (TIBC) and compared before and after therapy. Results: The mean age group of the patients was 24.94 years. Majority of the patients were multipara (68%) and belongs to the class V socio economic status (84%). All the blood parameters were increased significantly (p=0.000) when compared from baseline values to end of the treatment. Mean raise in haemoglobin% after 30 days of treatment was 3.60. Average raise in the mean hematocrit was 8.73. The mean difference in the mean corpuscular volume, total iron binding capacity and the percent saturation was 129.77, 13.55, was 22.26 respectively. Conclusions: Our data confirm that the intravenous iron sucrose was very effective, well tolerated and safe than other forms of iron preparations for treating iron deficiency anaemia in postnatal women.